Um percurso do uso das tecnologias de informação e comunicação (TICS) nas escolas públicas municipais de ensino fundamental - anos iniciais de Toledo/Pr - Nakamura, Dulce Alves da Silva (2016)
This study aims to investigate the use and the process of integration of Information and Communication Technologies (ICTs) in education in public schools - the early years of the city of Toledo / PR. The methodology used was a qualitative approach and gathered a bibliographic study on the subject, as well as carrying out semi-structured interviews and printed questionnaire. The theoretical framework of this study is based on authors who work with the issue of ICTs in education, from Manuel Castells, Pierre Lévy, Jesús Martin-Barbero, Marta Gabriel, Maria Luiza Belloni, Vani Moreira Kenski. Regarding the use of oral sources were used as a means to supplement the documentary information. To obtain the data was a questionnaire with 25 questions to 60 teachers of the municipal network. The questioned were delivered as follows: in a meeting held by the Municipal Department of Education, were given randomly 100 questionnaires the directors of the 36 municipal schools, which passed on to teachers; through them, we got important information from the professional group and individual use, school structure, organizational laboratories or computer rooms, availability and access, within others. These data, along with officials of Amop and municipal Secretariat, allowed us to make an analysis on digital migrants and the use they make of technology as a means of production of teaching.